Guinea- Bissau : 2017 Article IV Consultation and Fourth Review Under the Extended Credit Facility Arrangement, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Guinea-Bissau. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Guinea-Bissau's commitment to the Extended-Credit-Facility-supported program is strong and the results are apparent. The economy is growing strongly and the fiscal position has improved markedly. Supported by favorable terms of trade, real GDP growth averaged almost 6 percent in 2015-16, with a surplus on the external current account and inflation below 2 percent a year. Public financial management has improved and the 2017 fiscal deficit is projected to fall under 2 percent of GDP. The outlook is broadly favorable, with growth projected at 5 percent over the medium term.